Perkembangan Rasionalisme Modern pada Abad Renaisans - Folandra, Danil; Suhendra, Alhamdi; Ahmad, Fandy Ummanah (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This article describes the development of modern rationalism in the renaissance century which focuses on philosophers: Descartes, Spinoza, and Leibniz, and Pascal. This article is a qualitative article which is analyzed using descriptive, explorative and analytical methods. This article finds data that modern rationalism in the renaissance century was marked by the thoughts of three great figures namely Descartes, Spinoza, and Leibniz, who created the rise of the use of reason as a tool to gain knowledge. While Pascal has another view that the element of the heart is often far more important than the element of ratio. For Pascal, getting knowledge is obtained in two ways, the mind and the heart, and the heart has its own logic. The three Rationalists based their philosophy on the concept of substance, but they differed in the relationship between soul and matter and the amount of substance. Descartes mentions that there are three substances: God, soul and matter, Spinoza only recognizes God. Meanwhile, for Leibniz, the substance is God and the monades (family of souls). Meanwhile, Pascal's thought is to see that humans are creatures that need God, because the only way to understand humans is through religion.